First Miocene megafossil of arrowhead, alismataceous plant Sagittaria, from South America - Robledo, Juan Manuel (2021)
The first pre-Quaternary representative of Alismataceae from South America is reported based on achenes of Sagittaria montevidensis from the Palo Pintado Formation (upper Miocene) in the south of Salta Province, Argentina. Achenes are laterally compressed, have a lateral beak and a single recurved seed inside them. The fruits were found both in the base (10 Ma) and the top of the formation (~5 Ma), suggesting similar environmental conditions during this time period. A cursory review of the Alismataceae family in the fossil record, with a special interest in those South American reports is given. During the Oligocene-Miocene Sagittaria may have arrived from tropical Africa to South America and thence to North America.